Testicular endothelial cells are a critical population in the germline stem cell niche. Issue 1 (December 2018) - Bhang, Dong; Kim, Bang-Jin; Kim, Byung; Schadler, Keri; Baek, Kwan-Hyuck; Kim, Yong; Hsiao, Wayland; Ding, Bi-Sen; Rafii, Shahin; Weiss, Mitchell; Chou, Stella; Kolon, Thomas; et al.
Abstract Maintenance of adult tissues depends on stem cell self-renewal in local niches. Spermatogonial stem cells (SSC) are germline adult stem cells necessary for spermatogenesis and fertility. We show that testicular endothelial cells (TECs) are part of the SSC niche producing glial cell line-derived neurotrophic factor (GDNF) and other factors to support human and mouse SSCs in long-term culture. We demonstrate that FGF-2 binding to FGFR1 on TECs activates the calcineurin pathway to produce GDNF. Comparison of the TEC secretome to lung and liver endothelial cells identified 5 factors sufficient for long-term maintenance of human and mouse SSC colonies in feeder-free cultures. Male cancer survivors after chemotherapy are often infertile since SSCs are highly susceptible to cytotoxic injury. Transplantation of TECs alone restores spermatogenesis in mice after chemotherapy-induced depletion of SSCs. Identifying TECs as a niche population necessary for SSC self-renewal may facilitate fertility preservation for prepubertal boys diagnosed with cancer. Self-renewal of spermatogonial stem cells (SSC) is necessary for spermatogenesis and male fertility. Here the authors identify testicular endothelial cells (TECs) as a source of 5 key growth factors for self-renewal and expansion of human and mouse SSCs.